An Analysis of Translation Errors (A case Study of Students at SMAN 2 Wawonii Tenggara) - Yeni Yeni; Tambunan Tambunan; La Ino (Journal of Language Education and Educational Technology (JLEET), 2024)
This study examined the errors made by students in translating Indonesian into English using the surface category taxonomy. The research was conducted at SMAN 2 Wawonii Tenggara, focusing on first-grade students. Specifically, the research included all 20 students from class X.IPA. To gather data, the researcher employed a test consisting of 20 Indonesian sentences. The analysis was carried out using a qualitative descriptive method. The results indicated that the students made a total of 222 errors (55.5%) in translating Indonesian into simple English sentences. These errors were categorized into four types: omission errors (112 or 50.45% of the total), malformation errors (75 or 33.79%), addition errors (32 or 14.41%), and misordering errors (3 or 1.35%). Omission errors were the most frequent. Given that the students made 222 errors (55.5% of possible errors), the correct responses numbered 178 (44.5%). According to Rod Ellis, this number classifies the students' ability as poor.